IMPACT OF INFLATION AS A CREDIT RISK MODERATOR ON THE PROFITABILITY OF INDONESIAN BANKING SECTOR - Abdul Haris; Dev Anand; Erwin Budianto (Jurnal Ekonomi, 2023)
The purpose of this study is to determine the signification of factors that affect the company's profitability through the Inflation factor as a moderation variable. The research method used is a quantitative research method. The population in this study of financial institutions in the banking sector in Indonesia is conventional commercial banks and observational data during 2016 - 2020. The sampling measurement technique uses purposive sampling. The sampling technique uses secondary data, namely published financial statements. The data analysis technique used is to use descriptive statistical analysis before and after the existence of interactive variables, then followed by multiple regression and testing moderation variables all variables tested using the entered method. The results of the study explained that before the moderation variable, namely the credit risk interaction variable, it had an insignificant effect on profitability.